Making a dent in human trafficking: investigating the effects of social institutions and policies across 60 countries - Kabbash, Laura A. (Crime, law and social change, 2021)
Given the worldwide magnitude, pervasiveness and deleterious consequences of human trafficking (Roth, 45), a more comprehensive understanding of its underlying causes is imperative. This study attempted to examine the influence of three social factors (i.e., economics, social capital, and criminal justice) on human trafficking in 60 countries. Although regression and Bayesian analyses showed that macro level economic, social, and criminal justice factors were not predictive of human trafficking, our findings highlighted the variability and potential inaccuracy in reporting of information in many countries. Many factors contribute to unreliable human trafficking data including: (1) inconsistencies in the application of trafficking legislation, (2) problems with victim identification and reporting, (3) varying definitions and counts of trafficking, (4) the creation of cultural binaries in the media, and (5) problematic human-trafficking policies. To accurately identify factors contributing or maintaining human trafficking, it is critical for governmental and non-governmental agencies to collect a range of standardized information.